The Robustness Reproducibility of the American Economic Review - Douglas Campbell; Abel Brodeur; Anna Dreber; Magnus Johannesson; Joseph Kopecky; Lester Lusher; Nikita Tsoy (Institute for Replication (I4R), 2024)
We estimate the robustness reproducibility of key results from 17 non-experimental AER papers published in 2013 (8 papers) and 2022/23 (9 papers). We find that many of the results are not robust, with no improvement over time. The fraction of significant robustness tests (p﹤0.05) varies between 17% and 88% across the papers with a mean of 46%. The mean relative t/z-value of the robustness tests varies between 35% and 87% with a mean of 63%, suggesting selective reporting of analytical specifications that exaggerate statistical significance. A sample of economists (n=359) overestimates robustness reproducibility, but predictions are correlated with observed reproducibility.
Keywords: 330